PENGARUH PRILAKU DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT TRI PRIMA PALEMBANG - Januar Ida Wibowati (Ekonomika, 2021)
This study aims to determine the effect of discipline behavior and work environment on the performance of PT Tri Prima Palembang employees. The population in this study were all employees of PT Tri Prima Palembang, totaling 63 people. The sampling technique is the Accidental Sampling technique, data analysis using validity, reliability, classical assumption test, multiple regression analysis, t test and F test. The results show that work discipline has a positive and significant effect of 1.433, work environment has a positive effect and significant at 1.012 to the performance of employees of PT Tri Prima Palembang. . The results of the regression calculation show that the coefficient of determination (R square) is 0.478 or 47.8%. This means that the variables of work discipline and work motivation are able to explain the variation in the performance of PT Tri Prima Palembang employees by 47.8%, while the remaining 52.2% is explained by other variables outside this study.